2020
DOI: 10.1111/acel.13116
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic correction of Werner syndrome gene reveals impaired pro‐angiogenic function and HGF insufficiency in mesenchymal stem cells

Abstract: WRN mutation causes a premature aging disease called Werner syndrome (WS). However, the mechanism by which WRN loss leads to progeroid features evident with impaired tissue repair and regeneration remains unclear. To determine this mechanism, we performed gene editing in reprogrammed induced pluripotent stem cells (iPSCs) derived from WS fibroblasts. Gene correction restored the expression of WRN. WRN+/+ mesenchymal stem cells (MSCs) exhibited improved pro‐angiogenesis. An analysis of paracrine factors reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Our findings showed that WRN was expressed during the early stage of pluripotency and was specifically up-regulated during chondrocyte differentiation. Ablation of WRN did not affect the pluripotential status, which has been corroborated by the previous studies 37 . However, upon differentiation into multipotent MSCs, the differentiating ability was impaired by WRN loss somehow.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our findings showed that WRN was expressed during the early stage of pluripotency and was specifically up-regulated during chondrocyte differentiation. Ablation of WRN did not affect the pluripotential status, which has been corroborated by the previous studies 37 . However, upon differentiation into multipotent MSCs, the differentiating ability was impaired by WRN loss somehow.…”
Section: Discussionsupporting
confidence: 88%
“…Together, these data suggest that the cells became a population enriched specifically for mesendodermal growth. It has been reported that the loss of WRN did not affect the pluripotency of induced stem cells (iPSCs); however, upon differentiation into the mesenchymal lineage, the differentiation ability of WRN −/− iPSCs was influenced 37 . We hereby continued to examine the differentiation at stage 3 where the CTR cell clusters were distributed throughout the culture and stained in dark blue, indicating the existence of an extracellular matrix, which is a necessary prerequisite for chondrocyte formation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the original publication of J. Tu et al, (2020), the Materials and Methods section was not included. The missing section is shown below.…”
mentioning
confidence: 99%
“…We have previously characterized the transcriptomic difference between iPSC-derived, isogenic WRN +/+ and WRN −/− mesenchymal stem cells (MSC). Downregulation of paracrine factors such as HGF accounts for the impaired pro-angiogenic function in WRN −/− MSC [ 7 ]. Notably, we also found downregulation of short stature homeobox ( SHOX ) gene in the WRN-deficient cells.…”
Section: Introductionmentioning
confidence: 99%